Flightless Notaris (Coleoptera: Curculionidae: Brachycerinae: Erirhinini) in Southwest China: monophyly, mtDNA phylogeography and evolution of habitat associations - Grebennikov, Vasily V.; Kolov, Sergey V. (Zootaxa, 2016)
This paper reports the recent discovery of flightless populations of weevils of the genus Notaris in Yunnan and Sichuan provinces of China. Specimens were found in the middle or high altitude mountains (2440–4195 m), by either sifting leaf litter in the deciduous forest and among alpine Rhododendron shrubs, or by turning rocks in the alpine zone. These finds extend southwards the Asian range of this Holarctic genus and report its highest altitudinal records. DNA barcodes of 127 specimens were phylogenetically analysed, of them 42 are those of newly discovered Notaris from Southwest China. The genera Notaris and Tournotaris consistently formed a clade, with Tournotaris nested inside Notaris in Maximum Parsimony (MP) and Maximum Likelihood (ML) analysis. The newly discovered flightless Notaris from Southwest China were either monophyletic (MP) or paraphyletic with respect to volant Holarctic N. aethiops (ML); the latter placement being likely an artefact. A strict linear molecular clock approach suggests a pre-Pliocene separation of Notaris populations in Southwest China. Habitat associations of these high-altitude flightless Notaris contrast sharply with that of the predominantly volant lowland riparian Notaris and other Erirhinini. We hypothesis that evolution of habitat selection in Notaris went from lowland riparian, to high altitude (via uplift of the Tibetan Plateau and adjacent regions of Central Asia), and then to forest leaf litter (via subsequent erosions of isolated mountains such as Emei Shan in Sichuan losing the alpine zone and forcing Notaris into the forest floor). Taxonomic uncertainty of Asian Notaris is addressed and remains unresolved due to uninformative morphology and conflicting DNA signal. Identities of two obscure and likely closely related species, Notaroides brevirostris and Notaris kozlovi from nearby SE Qinghai and NW Sichuan, respectively, are discussed and illustrated. Pending further research, all reported flightless Notaris from Yunnan and Sichuan are hypothesised to form a clade, for which the available name N. kozlovi is used. Habitus and genitalia of Notaris specimens from the newly detected populations are illustrated.